2008
DOI: 10.1002/msc.138
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis patients' knowledge of the disease and its treatments: A descriptive study

Abstract: RA patients' knowledge of their disease and its treatments varied from poor to good in this group. These results can be used for advancing RA patient education. However, more research is needed to evaluate RA patients' knowledge levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 25 publications
2
35
0
1
Order By: Relevance
“…33 The studies did not reveal a correlation between the level of knowledge of patients and their physical functioning in everyday life. The autors' own study showed, however, that the level of knowledge about the disease affected the SF domain in the SF-36 questionnaire.…”
Section: Discussionmentioning
confidence: 81%
“…33 The studies did not reveal a correlation between the level of knowledge of patients and their physical functioning in everyday life. The autors' own study showed, however, that the level of knowledge about the disease affected the SF domain in the SF-36 questionnaire.…”
Section: Discussionmentioning
confidence: 81%
“…As multi-professional education is offered to patients, [5] nurses also seemed to want education that was similarly derived. RA has a considerable impact upon the patients' quality of life, [4] and thus the needs of patients also require ever-widening areas of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, rheumatology or district nurses with physicians monitor the patient in health centres when the RA is in remission. [5] Very few RA patients undergo primary admission to hospital wards due to RA, but as a secondary diagnosis RA is rather common. The Finnish Medical Society Duodecim (2009) [6] has published national Current Care Guidelines concerning RA but it's focus is mainly on medical information and treatment of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients with rheumatic conditions need to take a number of different drugs. In order for the treatment to be knowledge of disease and treatment differs (Mäkeläinen et al, 2009a;Sierakowska, 2005). Following hospitalization, patients have insuffi cient knowledge about their medications.…”
Section: Introductionmentioning
confidence: 99%
“…Three-quarters of rheumatology nurses (n = 80) gave patients information about anti-rheumatic drugs and only 15% of the nurses also gave information about non-steroidal anti-infl ammatory drugs (NSAIDs) (Mäkeläinen et al, 2007). Patients with rheumatoid arthritis (RA) were found to have a moderate knowledge of how to use anti-rheumatic drugs and NSAIDs (Mäkeläinen et al, 2009a) and about half of the patients (n = 173) were satisfi ed with patient education given by rheumatology nurses. The patients who were dissatisfi ed felt that the rheumatology nurses had not tailored the information to their needs (Mäkeläinen et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%